7+m+9(6m-3)=

Simple and best practice solution for 7+m+9(6m-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+m+9(6m-3)= equation:


Simplifying
7 + m + 9(6m + -3) = 0

Reorder the terms:
7 + m + 9(-3 + 6m) = 0
7 + m + (-3 * 9 + 6m * 9) = 0
7 + m + (-27 + 54m) = 0

Reorder the terms:
7 + -27 + m + 54m = 0

Combine like terms: 7 + -27 = -20
-20 + m + 54m = 0

Combine like terms: m + 54m = 55m
-20 + 55m = 0

Solving
-20 + 55m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + 55m = 0 + 20

Combine like terms: -20 + 20 = 0
0 + 55m = 0 + 20
55m = 0 + 20

Combine like terms: 0 + 20 = 20
55m = 20

Divide each side by '55'.
m = 0.3636363636

Simplifying
m = 0.3636363636

See similar equations:

| 8x+14=8x+14 | | 8(x+14)=8x+112 | | -29=4(u-8)-7u | | 5c-15=2c+5 | | 102.569-10.478= | | 12d-40=8 | | 2x+14=-8x-18 | | 2x+14=2x-18 | | 5n+16=n-8 | | s^3-510=0 | | 0=3x+9 | | 8c-3(c+4)=43 | | (x-6)/14=(7x)/21 | | 5x-18=2x+30 | | 2x^2+3y^2=30 | | 7+18/(6-3) | | 4(t-6)+8t=6(2t+4)-12 | | 5x^2+30x+150=1220 | | 5x+15=220000 | | -30=5+5u | | (3x/7)+3=24 | | x/6+8=26 | | -1/3m-4=22 | | 3m+15+2m-15=7m+15 | | 360*67/72*11/25 | | 2(2-4x-9x)+6(5x+2)=28 | | 5z-18z= | | 3(x-3)-5=16 | | 4x+5=5x+5 | | 0.04x+4=40 | | 4x-3=4x-3 | | 4(-8x+5)= |

Equations solver categories